Boccaccio's Fabliaux : Medieval Short Stories and the Function of Reversal - Brown, Katherine Adams, 1978- (Book collections on Project MUSE., 2014)
Provides a new and provocative interpretation of the relationship between medieval French fabliaux and Boccaccio's Decameron, examining their formal similarities.